Comparison of Clinico-radiologic Outcome of Direct Palatal Vault Plating as against CAD/ CAM-assisted Patient-specific Palatal Splint in Patients with Palatal Fractures of Maxilla: A Protocol for Randomised Clinical Trial - Rozina Vishnani; Nitin Bhola (Journal of Clinical and Diagnostic Research)
Introduction: Palatal fractures are associated with Le Fort fractures and have an incidence ranging from 8 to 46.4%. They rarely occur in isolation and are typically treated using either a closed or open method. Need of the Study: The closed method, although less invasive and simple, has drawbacks such as bone mismatch since the fractures are not directly visualised and the stability of wires used is questionable. On the other hand, the open method is considered the gold standard but is a complex technique with drawbacks like wound dehiscence and implant exposure. In this study, we are introducing a newer modality, Computer-Aided Design (CAD)/Computer-Aided Manufacturing (CAM)-assisted Patient-specific Palatal Splint (CAPSPS), which aims to combine the simplicity of the closed method with the precision of reduction seen in the open method. Aim: To evaluate and compare the clinical and radiologic outcomes of direct palatal vault plating against CAPSPS in patients with palatal fractures of the maxilla. Materials and Methods: The current prospective, interventional, randomised parallel-arm controlled trial will be conducted at Department of Oral and Maxillofacial Surgery, Sharad Pawar Dental College, Wardha, Maharashtra, India, from July 2023 to July 2026 which will include 60 patients with palatal fractures of the maxilla. The patients will be randomly assigned to two groups using computer-generated randomisation. Group-A comprising 30 patients will undergo treatment with direct palatal vault plating, while 30 patients in Group-B will be treated with CAPSPS. Clinical outcomes, including fracture stability and occlusion, will be assessed intraoperatively and at one week, one month, third month and 6-month follow-up. Radiologic outcomes will be evaluated using Computed Tomography (CT) scans, with reduction and midface width assessed at the one week and six months. Scales proposed for assessing clinical and radiologic outcomes will be validated during the study. Intraoperative and postoperative complications will be qualitatively assessed and the intraoperative time will be compared between the two groups. Data will be recorded in a Microsoft Excel sheet and analysis will be conducted using Statistical Package for the Social Sciences (SPSS) version 23.0 software. Group comparisons to determine outcomes will be assessed using the independent sample t-test for continuous data with a normal distribution and the Chi-square test for identifying relationships between variables. Repeated measures Analysis of Variance (ANOVA) will be employed at different time intervals within both Group-A and Group-B. The statistical significance level will be set at p<0.05.